Impacto de la gestión de desempeño en una institución estatal peruana para mejorar la inversión pública en infraestructura educativa - Calopino Arellano, César Jarzinhio (2024)
The objective of this paper was to analyze the impact of performance management in a government institution to improve school educational infrastructure during the period 2015-2022. The Programa Nacional de Infraestructura Educativa (PRONIED) is the institution tasked with ensuring the good management of public investment for the maintenance, replacement and improvement of school infrastructure throughout Peru, so its management should be reviewed based on the objectives and results of institutional performance indicators during the period of its operation. The research used the applied method with a longitudinal design and quantitative approach. Likewise, the sample used was quantitative, drawn up through data series obtained from the performance indicators extracted from the government website. The results obtained confirm the hypotheses based on the premise that institutional performance management has an impact on public investment in school infrastructure. Thus, the existence of statistical veracity is confirmed at a moderate level (with R2 = 68%) related to the linearity or relationship between the Public Investment Processes in Educational Infrastructure (PIP) and the institutional performance management of PRONIED (represented by preventive and corrective maintenance activities, as well as completed projects). The overall conclusion is that there is a significant impact of public investment in educational infrastructure on PRONIED's performance management.